Dental knowledge and self-reported oral care practices among medical, pharmacy and nursing students - Tuti Ningseh Mohd-Dom,; Shahida Mohd Said,; Zamirah Zainal Abidin, (Penerbit UKM, 2009)
A self-administered questionnaire survey was conducted to investigate the level of dental knowledge among senior medical, pharmacy and nursing students of Universiti Kebangsaan Malaysia, and to determine self-reported practices of oral care. Students were invited to complete a set of questionnaires on knowledge related to causes, prevention, signs and treatment of dental caries and periodontal disease; and practices related to oral hygiene and dental visits. A total of 206 questionnaire forms were distributed. 204 forms were returned complete (response rate = 99%). Dental knowledge scores ranged from 0 (no correct answer given) to 16 (gave all correct answers). The mean knowledge scores between the groups were statistically different (p < 0.05): pharmacy students scored highest (mean = 12.29, 95% CI 11.44, 13.14) followed by the medical students (mean = 12.02, 95% CI 11.33, 12.71) and nursing students (mean = 10.83, 95% CI 10.40, 11.26). Areas that had lowest knowledge scores were signs and treatment of gum disease. With regard to oral care practices, majority cited that they brushed teeth at least twice a day (94.6%) and used toothbrush and toothpaste (97.5%). Not many (21.8%) used dental floss and about half (54.2%) reported visiting the dentist more than twelve months ago. Reasons for dental visits included getting check-ups (64.6%), restorations (45.6%) and emergency care such as extractions (24.0%). In general students had at least a moderate level of dental knowledge but demonstrated poor knowledge in some areas. While most reported good oral hygiene habits, behaviour related to dental visits need to be improved. Findings suggest a need for inclusion of oral health education in the medical, pharmacy and nursing curriculum.